2022
DOI: 10.1136/bmjopen-2021-056951
|View full text |Cite
|
Sign up to set email alerts
|

Indirect effects of the early phase of the COVID-19 pandemic on the coverage of essential maternal and newborn health services in a rural subdistrict in Bangladesh: results from a cross-sectional household survey

Abstract: ObjectiveThis paper presents the effect of the early phase of COVID-19 on the coverage of essential maternal and newborn health (MNH) services in a rural subdistrict of Bangladesh.DesignCross-sectional household survey with random sampling.SettingBaliakandi subdistrict, Rajbari district, Bangladesh.ParticipantsData were collected from women who were on the third trimester of pregnancy during the early phase of the pandemic (111) and pre-pandemic periods (115) to measure antenatal care (ANC) service coverage. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…These disruptions have led to worrisome impacts, including a decrease in vaccination (i.e., one-fourth of newborn babies were not vaccinated during the pandemic [ 12 ]) and increased child deaths (12.8%) and maternal deaths (7.6%) [ 9 ]. Similar disruptions have been reported in other studies focusing specifically on rural sub-districts or urban areas [ 14 ]. In addition, a qualitative study of 15 pregnant women in Khulna revealed how they experienced socioeconomic hardships (loss of income, difficulty in receiving loans, and a lack of transportation) and emotional distress (fear, worry, and sadness [ 10 ]).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…These disruptions have led to worrisome impacts, including a decrease in vaccination (i.e., one-fourth of newborn babies were not vaccinated during the pandemic [ 12 ]) and increased child deaths (12.8%) and maternal deaths (7.6%) [ 9 ]. Similar disruptions have been reported in other studies focusing specifically on rural sub-districts or urban areas [ 14 ]. In addition, a qualitative study of 15 pregnant women in Khulna revealed how they experienced socioeconomic hardships (loss of income, difficulty in receiving loans, and a lack of transportation) and emotional distress (fear, worry, and sadness [ 10 ]).…”
Section: Introductionsupporting
confidence: 89%
“…The triangulation of the survey data and interviews with pregnant women confirmed these fears. On the one hand, two in five households restrained from seeking healthcare due to fears of infection [ 12 ], and pregnant women avoided ANC visits, especially in the third trimester [ 14 ]. On the other, pregnant women expressed that their risk assessments involved emotional distress but also socioeconomic hardships, such as a loss of income [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico, for example, the Mexican Institute of Social Security contracted out private hospitals to provide childbirth services so that public hospital beds could be used for covid-19 patients 15. Service delivery data from Bangladesh documented that the private sector was able to maintain pre-pandemic population level service coverage of facility based delivery, antenatal care, and postnatal care services at the beginning of the pandemic 16…”
Section: Private Sector Engagement Can Improve Qualitymentioning
confidence: 99%
“…Moreover, the coronavirus disease (COVID-19), emerging from the Hubei Province in the People’s Republic of China in December 2019 and subsequently spreading throughout the world, has resulted in alterations to healthcare structures and processes, such as reduced maternity service provision, including PNC [ 7 , 8 , 9 , 10 , 11 , 12 ]. However, to our knowledge, only a few studies have examined the PNC uptake using a quantitative approach during the pandemic in Ethiopia [ 13 ], Bangladesh [ 14 ], and the UK [ 15 ].…”
Section: Introductionmentioning
confidence: 99%